Could gastric histology be a useful marker for making decision on Helicobacter pylori eradication therapy in patients with dyspepsia? É a histologia gástrica um marcador útil na decisão de erradicar o Helicobacter pylori nos pacientes com dispepsia? - Severino Marcos Borba de Arruda (Arquivos de Gastroenterologia, 2009)
CONTEXT: It still remains an open debate whether Helicobacter pylori eradication is beneficial or not for the improvement of symptoms in functional dyspepsia. Differences in geographic distribution, the worldwide H. pylori genetic variability and the fact that the outcome of infection is strongly related to the virulence of the infecting strain are factors that might be driving ongoing controversies. OBJECTIVE: To study the correlation between gastric histology and H. pylori serology status in patients with dyspepsia. METHODS: This is a cross-sectional study where 40 consecutive dyspeptic patients (28 women and 12 men, mean age 48.5 years) with endoscopically normal stomachs were selected from the endoscopy unit at a university hospital in Recife, PE, Northeast of Brazil, between March 1998 and July 1999. Patients underwent gastric mucosal biopsy and serological tests (anti-Hp and anti-CagA antibodies). Gastric biopsies were examined using H-E and Giemsa stains and gastritis was classified and graded (mild, moderate or severe) according to "the updated Sydney System - Houston, 1994". RESULTS: Among 40 patients with dyspepsia the gastric histology revealed that about ¼ had moderate (25%) or severe (2.5%) gastritis. This subgroup of patients also had a greater positive frequency of anti-Hp (100% vs 41%; P = 0.0005) and anti-CagA (91% vs 58%; P = 0.09) antibodies when compared with those with normal histology (27.5%) or mild gastritis (45%). CONCLUSION: Since upper gastrointestinal endoscopy is part of the functional dyspepsia investigation and serology for anti-CagA antibody is not available in daily clinical practice, by biopsying gastric mucosa we would only be able to selectively apply H. pylori eradication therapy for those with histology that best correlate with virulent infecting strains (moderate or severe gastritis) - around ¼ of our study patients with dyspepsia. CONTEXTO: O benefício da terapia de erradicação do H. pylori como parte do tratamento da dispepsia funcional ainda é uma questão em aberto. Diferenças na distribuição geográfica, a ampla variabilidade genética e o fato de que a expressão clínica da infecção está fortemente relacionada com a virulência das cepas infectantes, são fatores que provavelmente guiam as controvérsias. OBJETIVO: Estudar a correlação entre histologia gástrica e sorologia para H. pylori em doentes com dispepsia. MÉTODOS: Estudo descritivo-transversal com 40 pacientes consecutivos com sintomas dispépticos (28 mulheres e 12 homens, média de idade de 48,5 anos) e achado endoscópico de estômago normal, selecionados a partir da sala de endoscopia (Hospital das Clínicas da Universidade Federal de Pernambuco, Recife, PE.) entre março de 1998 e julho de 1999. Todos foram submetidos a biopsias gástricas e testes sorológicos (anti-Hp e anti-CagA). As biopsias foram analisadas pelos métodos de H-E e Giemsa e os achados de gastrite classificados de acordo com o Sistema Sydney atualizado. RESULTADOS: A histologia dos 40 pacientes revelou que cerca de ¼ apresentava gastrite moderada (25%) ou severa (2,5%). Esse grupo também apresentava maior frequência de positividade anti-Hp (100% vs 41%; P = 0,0005) e anti-CagA (91% vs 58%; P = 0,09) quando comparado com os casos com histologia normal (27,5%) ou gastrite leve (45%). CONCLUSÃO: Considerando que a endoscopia digestiva alta é parte da rotina de investigação da dispepsia funcional e que a sorologia anti-CagA não está disponível na prática clínica diária, através da histologia pode-se selecionar e aplicar terapia de erradicação do H. pylori apenas para os casos que muito provavelmente estão associados a cepas patogênicas de H. pylori (doentes com gastrite moderada ou severa) - cerca de ¼ da presente amostra.